Degradable PPE / PBT / PBS alloy material and preparation method thereof

By introducing specific proportional auxiliary agents into PPE/PBT/PBS alloy materials, the shortcomings in the performance and cost of existing regenerated and degradable plastics are solved, and high-performance and fully degradable degradable PPE/PBT/PBS alloys are achieved. Material.

CN119463427APending Publication Date: 2025-02-18HUNAN HENGYI NEW MATERIAL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410661469.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing recycled and degradable plastics have shortcomings in performance and cost, making it difficult to meet the needs of high toughness, flame retardancy and complete degradation.

Method used

PPE/PBT/PBS alloy materials are used, and through specific ratios and process treatments, compatibilizers, photooxygen degraders, nanotitanium dioxide and other auxiliary agents are introduced to form high-performance degradable materials.

Benefits of technology

The complete degradation of alloy materials in biological and composting environments is achieved, and it has high impact resistance, flame retardancy, fluidity, wear resistance and temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite material processing, and discloses a degradable PPE / PBT / PBS alloy material, which is prepared from the following components in parts by weight: 5 to 30 parts of PPE, 20 to 65 parts of PBT, 20 to 60 parts of PBS, 5 to 20 parts of compatilizer master batch, 5 to 30 parts of light-oxygen degradation master batch, 2 to 10 parts of PVA, 0.1 to 3 parts of SiC, 1 to 10 parts of nano titanium dioxide, 0.5 to 8 parts of BPO, 5 to 18 parts of polyglycolic acid, 0.5 to 8 parts of anti-hydrolysis agent, 0.5 to 10 parts of CaCO3 and 1 to 10 parts of super absorbent resin SAP. The degradable PPE / PBT / PBS alloy material prepared by the invention has relatively good impact resistance, flame retardance, flowability, wear resistance and temperature resistance, and has complete degradability in biological and compost environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite material processing, and in particular to a degradable PPE / PBT / PBS alloy material and a preparation method thereof. Background Art

[0002] According to data, global plastic emissions may reach 53 million tons in the future. Reducing or stopping the use of plastics, degrading plastics, preparing recycled plastics, and researching new environmentally friendly materials that can replace plastics are promising ways to solve the above problems.

[0003] Recycled plastics are processed and transformed from waste plastics by physical or chemical methods such as pretreatment and furnace forging. Recycled plastics are highly selective. Specifically, under the premise of low cost, according to different performance requirements, certain properties of waste plastics can be processed separately to produce products that meet the requirements. However, due to recycling, the performance of recycled plastics is getting worse and worse, and they can only be used in some fields with low requirements for hygiene and performance.

[0004] Degradable plastics are materials that can be decomposed into environmentally friendly substances by microorganisms under natural conditions after use. The main degradation methods are biodegradation, photodegradation, water degradation, and photo-biodegradation. However, compared with other plastics, the production cost of degradable plastics is very high, which limits the application of this material.

[0005] The raw materials of degradable plastics include bio-based and petroleum-based. Among them, the bio-based ones mainly include polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and the petroleum-based ones mainly include polybutylene succinate (PBS) and polybutylene terephthalate (PBT).

[0006] PBT (chemical formula is [(CH)4OOCCH4COO] n ), is a milky white translucent to opaque crystalline thermoplastic polyester with high heat resistance, toughness, fatigue resistance, low water absorption, etc. This material still maintains electrical properties in a humid environment and has excellent electrical insulation. However, PBT has defects such as low notched impact strength, large molding shrinkage, easy warping of products, easy corrosion by halogenated hydrocarbons, rapid crystallization at low temperatures, and poor water stability (easy to decompose in water).

[0007] PBS (chemical formula is H-[O(CH2)4OOC(CH2)2CO] n-OH), and the structural unit contains an ester group that is easily hydrolyzed. Under conditions such as composting and contact with specific microorganisms, it is easily decomposed and metabolized by enzymes in various microorganisms, animals or plants in nature, and finally forms CO2 and H2O, thus avoiding environmental pollution; in addition, the chemical structure, molecular weight, morphological distribution, melting point, and crystallinity of PBS molecules have different effects on the degradation process.

[0008] PPE (polyphenylene ether resin) is a non-toxic, transparent, low-density general-purpose engineering plastic with excellent mechanical strength, good dimensional stability, outstanding electrical insulation, good wear resistance, and heat resistance, water resistance, and water vapor resistance. However, PPE has high melt viscosity, poor melt fluidity, poor impact toughness, a tendency to stress cracking, and is difficult to process.

[0009] Based on the above problems, there is an urgent need for a high-performance alloy material with high toughness, high rigidity, low creep, impact resistance, wear resistance, high flame retardancy, and complete degradation during light and composting. Summary of the invention

[0010] The purpose of the present invention is to solve the above-mentioned technical problems and to provide a degradable PPE / PBT / PBS alloy material.

[0011] The technical solutions adopted are as follows:

[0012] The first aspect of the present invention provides a degradable PPE / PBT / PBS alloy material, which comprises the following components in parts by weight:

[0013] PPE 5-30 parts, PBT 20-65 parts, PBS 20-60 parts, compatibilizer masterbatch 5-20 parts, photo-oxidation degradation masterbatch 5-30 parts, PVA 2-10 parts, SiC 0.1-3 parts, nano titanium dioxide 1-10 parts, BPO 0.5-8 parts, polyglycolic acid 5-18 parts, anti-hydrolysis agent 0.5-8 parts, CaCO3 0.5-10 parts, super absorbent resin SAP 1-10 parts.

[0014] Preferably, the intrinsic viscosity of the PPE is 0.3-0.6 dl / g.

[0015] Preferably, the compatibilizer masterbatch comprises the following components in parts by weight: 40 parts of GMA-St-AN, 10 parts of PPE, 35 parts of PBT, 25 parts of PBS, 2 parts of maleic anhydride, 3 parts of BPO initiator, and 0.5 parts of benzoin;

[0016] The GMA-St-AN is a terpolymer of styrene-acrylonitrile-glycidyl methacrylate, and in the GMA-St-AN, the content ratio of styrene, acrylonitrile and glycidyl methacrylate is 8:70:22.

[0017] Preferably, the preparation method of the compatibilizer masterbatch is as follows:

[0018] The raw materials are weighed according to the weight ratio and put into a high-speed mixer, stirred at a speed of 300 rpm for 2 to 5 minutes, and after being evenly mixed, they are blended and extruded through a twin-screw extruder, cooled, pelletized, and dried; wherein the temperature of the twin-screw extruder is 200 to 250° C., and the screw speed is 35 to 55 Hz.

[0019] Preferably, the intrinsic viscosity of the PPE is 0.3-0.6 dl / g.

[0020] Preferably, the photo-oxidative degradation masterbatch comprises the following components in parts by weight: 70-85 parts of powder, 1-5 parts of PLA, 10-20 parts of PBAT, and 0.1-1 part of additives.

[0021] Preferably, the relative density of the PVA is 1.26-1.31 g / cm 3 , viscosity is 68.0~78.0.

[0022] Preferably, the nano titanium dioxide has an average particle size of 5 nm, a TiO2 content of 99.8%, and a specific surface area of ​​350 m 2 / g, bulk density is 0.2g / cm 3 .

[0023] Preferably, the melting point of the anti-hydrolysis agent is 50-53°C.

[0024] Preferably, the average particle size of the CaCO3 is 2000 mesh.

[0025] Preferably, the average particle size of the super absorbent resin SAP is 60-200 meshes.

[0026] The second aspect of the present invention provides a method for preparing the degradable PPE / PBT / PBS alloy material as described in the first aspect of the present invention, wherein the raw materials are weighed according to the weight ratio, put into a high-speed mixer for mixing, and then blended and extruded by a twin-screw extruder, cooled, pelletized, and dried;

[0027] The mixing treatment conditions at least meet the following requirements: the stirring speed is 300 rpm and the time is 2 to 5 min;

[0028] The parameter settings of the twin-screw extruder at least meet the following requirements: temperature is 190-250° C., and main engine speed is 35-45 Hz.

[0029] Beneficial effects of the present invention:

[0030] In the present invention, specific contents of PPE, PBT and PBS are selected as matrix materials, specific types of compatibilizer masterbatch are used as compatibilizers, and auxiliary agents such as photo-oxidative degradation masterbatch, PVA, SiC, nano-titanium dioxide, BPO, polyglycolic acid, anti-hydrolysis agent, CaCO3, and super absorbent resin SAP are introduced. After testing, the prepared degradable PPE / PBT / PBS alloy material has good impact resistance, flame retardancy, fluidity, wear resistance, temperature resistance, and is completely degradable in biological and composting environments. DETAILED DESCRIPTION

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] In the present invention, PLA is polylactic acid; PBAT is a thermoplastic biodegradable plastic, which is a copolymer of butylene adipate and butylene terephthalate; PVA is polyvinyl alcohol; BPO is dibenzoyl peroxide; and benzoin is dibenzoyl ketone.

[0033] It should be noted that, in various aspects of the present invention, for the same components in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.

[0034] As mentioned above, the first aspect of the present invention provides a degradable PPE / PBT / PBS alloy material, which comprises the following components in parts by weight:

[0035] PPE 5-30 parts, PBT 20-65 parts, PBS 20-60 parts, compatibilizer masterbatch 5-20 parts, photo-oxidation degradation masterbatch 5-30 parts, PVA 2-10 parts, SiC 0.1-3 parts, nano titanium dioxide 1-10 parts, BPO 0.5-8 parts, polyglycolic acid 5-18 parts, anti-hydrolysis agent 0.5-8 parts, CaCO3 0.5-10 parts, super absorbent resin SAP 1-10 parts.

[0036] According to a particularly preferred embodiment, the degradable PPE / PBT / PBS alloy material comprises the following components in parts by weight:

[0037] PPE 15-20 parts, PBT 30-50 parts, PBS 20-30 parts, compatibilizer masterbatch 8-10 parts, photo-oxidation degradation masterbatch 12-25 parts, PVA 2-3 parts, SiC 0.3-0.5 parts, nano titanium dioxide 1-2 parts, BPO 1.5-4 parts, polyglycolic acid 7-8 parts, anti-hydrolysis agent 2-3 parts, CaCO3 2-3 parts, super absorbent resin SAP 1.5-2 parts.

[0038] Preferably, the intrinsic viscosity of the PPE is 0.3-0.6 dl / g.

[0039] Preferably, the compatibilizer masterbatch comprises the following components in parts by weight: 40 parts of GMA-St-AN, 10 parts of PPE, 35 parts of PBT, 25 parts of PBS, 2 parts of maleic anhydride, 3 parts of BPO initiator, and 0.5 parts of benzoin;

[0040] The GMA-St-AN is a terpolymer of styrene-acrylonitrile-glycidyl methacrylate, and in the GMA-St-AN, the content ratio of styrene, acrylonitrile and glycidyl methacrylate is 8:70:22.

[0041] In the present invention, the compatibilizer masterbatch is an important component. The GMA-St-AN in the compatibilizer masterbatch can undergo a ring-opening reaction with PPE, PBT, and PBS, and open branched chains for ester exchange reaction. By using maleic anhydride, BPO initiator, and benzoin with specific contents as auxiliary materials, PPE, PBT, and PBS in the degradable PPE / PBT / PBS alloy material can be better fused and blended.

[0042] Preferably, the preparation method of the compatibilizer masterbatch is as follows:

[0043] The raw materials are weighed according to the weight ratio and put into a high-speed mixer, stirred at a speed of 300 rpm for 2 to 5 minutes, and after being evenly mixed, they are blended and extruded through a twin-screw extruder, cooled, pelletized, and dried; wherein the temperature of the twin-screw extruder is 200 to 250° C., and the screw speed is 35 to 55 Hz.

[0044] Preferably, the photo-oxidative degradation masterbatch comprises the following components in parts by weight: 70-85 parts of powder, 1-5 parts of PLA, 10-20 parts of PBAT, and 0.1-1 part of additives.

[0045] In the present invention, the photo-oxidative degradation masterbatch has a biodegradable function. Under the action of natural composting conditions (light, oxygen or heat), free radicals can be separated, so that the molecular weight of the polymer decreases sharply, the product quickly becomes brittle, and gradually decomposes into small fragments and tiny powders, and finally completely degrades into carbon dioxide, methane, water, inorganic minerals and other substances that are harmless to the environment.

[0046] Preferably, the relative density of the PVA is 1.26-1.31 g / cm 3 , viscosity is 68.0~78.0.

[0047] The PVA has good thermal stability. The substance does not change at a temperature of less than 140°C, begins to slowly turn yellow at a temperature of 160°C, undergoes intermolecular dehydration at 190-200°C, undergoes intramolecular dehydration at a temperature of more than 200°C, and completely decomposes at a temperature of more than 300°C. In addition, the PVA has good mechanical strength, a smooth and non-sticky surface, good solubility resistance, and a molecular film with good light transmittance, high moisture permeability, no electricity, no dust absorption, and good printability.

[0048] In the present invention, the PVA can be used as a modified dispersant, a compatibilizer, and an impact modifier. Together with the other technical features of the present invention, it can significantly improve the impact resistance, flame retardancy, fluidity, wear resistance, and temperature resistance of the degradable PPE / PBT / PBS alloy material, and make it completely degradable in a biological and composting environment.

[0049] In the present invention, the SiC can play a good deoxidation role in the polymerization process of the degradable PPE / PBT / PBS alloy material of the present invention.

[0050] Preferably, the nano titanium dioxide has an average particle size of 5 nm, a TiO2 content of 99.8%, and a specific surface area of ​​350 m 2 / g, bulk density is 0.2g / cm 3 .

[0051] In the present invention, the photocatalytic effect of the nano titanium dioxide can be stimulated under the irradiation of visible light, and the organic matter can be finally oxidized and decomposed into harmless substances such as CO2 and H2O without selectivity.

[0052] It should be noted that in the degradable PPE / PBT / PBS alloy material, the PPE is a non-crystalline polymer with excellent performance but difficult to decompose; the PBT and the PBS are both crystalline polymers, and blending the PPE, the PBT and the PBS is extremely incompatible. In the research process of the present invention, in order to solve the compatibility of the PPE, the PBT and the PBS, and to solve the degradation problem of the PPE, BPO is introduced as an initiator in the technical solution of the present invention to promote the cracking of the PPE, thereby preparing a degradable PPE / PBT / PBS alloy material with excellent performance to meet the needs of different fields.

[0053] In the present invention, the polyglycolic acid has good biodegradability and biocompatibility, and gradually degrades after a certain period of use, and finally turns into water and carbon dioxide. This material can greatly improve the degradation performance of the alloy material obtained by the present invention.

[0054] Preferably, the melting point of the anti-hydrolysis agent is 50-53°C.

[0055] The anti-hydrolysis agent can delay or prevent water decomposition by lowering the reaction temperature, increasing the reaction time, etc.; and the anti-hydrolysis agent can undergo a neutralization reaction with water molecules to form a stable complex with the raw material molecules. Therefore, the anti-hydrolysis agent can prevent further reaction between the raw material molecules and the water molecules, thereby reducing the reaction rate of water decomposition; secondly, the anti-hydrolysis agent can prevent hydrolysis reaction by inducing collision of molecular kinetic energy, causing interference, and breaking the chemical bonds between chains to form a new chemical bond, or forming a chemical bond that is easily decomposed by oxygen, water or other physical environmental factors.

[0056] In the present invention, in the process of preparing the degradable PPE / PBT / PBS alloy material, the anti-hydrolysis agent can effectively inhibit the decrease of mechanical properties caused by hydrolysis and dissolution, thereby achieving an effective anti-hydrolysis effect.

[0057] Preferably, the average particle size of the CaCO3 is 2000 mesh.

[0058] Preferably, the average particle size of the super absorbent resin SAP is 60-200 meshes.

[0059] Further preferably, the average particle size of the super absorbent resin SAP is 100-120 meshes. The inventors of the present invention have found that under this preferred condition, the super absorbent resin SAP has a stronger water absorption capacity, and combined with the other technical features of the present invention, the resulting degradable PPE / PBT / PBS alloy material has better impact resistance, flame retardancy, fluidity, wear resistance, temperature resistance, and is completely degradable in a biological and composting environment.

[0060] Further preferably, the pH value of the super absorbent resin SAP is 6 to 8. The inventors of the present invention have found that under this preferred condition, the super absorbent resin SAP has a stronger water absorption capacity, and combined with the other technical features of the present invention, the obtained degradable PPE / PBT / PBS alloy material has better impact resistance, flame retardancy, fluidity, wear resistance, temperature resistance, and is completely degradable in biological and composting environments.

[0061] As mentioned above, the second aspect of the present invention provides a method for preparing the degradable PPE / PBT / PBS alloy material as described in the first aspect of the present invention, wherein the raw materials are weighed according to the weight ratio, put into a high-speed mixer for mixing, and then blended and extruded by a twin-screw extruder, cooled, pelletized, and dried;

[0062] The mixing treatment conditions at least meet the following requirements: the stirring speed is 300 rpm and the time is 2 to 5 min;

[0063] The parameter settings of the twin-screw extruder at least meet the following requirements: temperature is 190-250° C., and main engine speed is 35-45 Hz.

[0064] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0065] In the following examples, PPE, with an intrinsic viscosity of 0.3-0.6 dl / g, was purchased from Nantong Xingchen Synthetic Materials Co., Ltd., with a brand name of LXN040;

[0066] PBT, purchased from China Petrochemical Corporation, brand BM434;

[0067] PBS, heat deformation temperature is 100℃, brand is FD92PB;

[0068] The photo-oxidative degradation masterbatch, calculated by weight, includes the following components: 70-85 parts of powder, 1-5 parts of PLA, 10-20 parts of PBAT, and 0.1-1 parts of additives, purchased from Yunfu Hongzhi New Materials Co., Ltd., with the brand name Hongzhi New Materials G-80;

[0069] PVA, relative density is 1.26~1.31g / cm 3 , viscosity 68.0-78.0, purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., brand PVA2699;

[0070] SiC, purchased from Hangzhou Jikang New Materials Co., Ltd., brand name: ultrafine silicon carbide;

[0071] Nano titanium dioxide, average particle diameter is 5nm, TiO2 content is 99.8%, specific surface area is 350m2 / g, bulk density is 0.2g / cm 3 , purchased from Nanjing Baoket New Materials Co., Ltd., brand name PTT-GA05;

[0072] BPO, purchased from Wanqing Chemical Technology Co., Ltd., brand name GB-50L;

[0073] Polyglycolic acid was purchased from Suzhou Qihang Biotechnology Co., Ltd.;

[0074] Anti-hydrolysis agent, melting point 50-53°C, purchased from Shenzhen Heyanyue Plastic Pigment Additive Co., Ltd., brand name Wuxingxing Anti-hydrolysis Agent;

[0075] CaCO3, purchased from Jiangxi Chenxin New Materials Co., Ltd., grade is heavy calcium carbonate 2000 mesh;

[0076] Super absorbent resin SAP, with an average particle size of 60-200 meshes, was purchased from Zhengzhou Guangyang Environmental Protection Technology Co., Ltd. with a brand name of XSSZ.

[0077] Example 1

[0078] A degradable PPE / PBT / PBS alloy material, comprising the following components in parts by weight:

[0079] PPE, PBT, PBS, compatibilizer masterbatch, photo-oxidation degradation masterbatch, PVA, SiC, nano titanium dioxide, BPO, polyglycolic acid, anti-hydrolysis agent, CaCO3, super absorbent resin SAP.

[0080] The compatibilizer masterbatch includes the following components by weight: 40 parts of GMA-St-AN, 10 parts of PPE, 35 parts of PBT, 25 parts of PBS, 2 parts of maleic anhydride, 3 parts of BPO initiator, and 0.5 parts of benzoin; in the GMA-St-AN, the content ratio of styrene, acrylonitrile, and glycidyl methacrylate is 8:70:22;

[0081] The preparation method of the compatibilizer masterbatch is as follows: weigh the raw materials according to the weight ratio, put them into a high-speed mixer, stir them at a speed of 300 rpm for 2 to 5 minutes, mix them evenly, then blend and extrude them through a twin-screw extruder, cool, pelletize and dry them; wherein the temperature of the twin-screw extruder is 200 to 250°C, and the screw speed is 35 to 55 Hz.

[0082] The preparation method of the degradable PPE / PBT / PBS alloy material is as follows (according to the formula and process parameters in Table 1):

[0083] The raw materials are weighed according to the weight ratio, added into a high-speed mixer for mixing (to fully mix them), and then blended and extruded through a twin-screw extruder, cooled, pelletized and dried.

[0084] Unless otherwise specified, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and Comparative Example 2 are carried out using the same process as Example 1, but the formulas and process parameters used are different, see Table 1 for details.

[0085] Table 1

[0086]

[0087] Test Example 1

[0088] The degradable PPE / PBT / PBS alloy materials prepared in the above examples and comparative examples were placed in a vacuum oven, dried at 100°C for 2 hours, transferred to an injection molding machine, injection molded at 190-250°C to obtain sample strips, and placed in an environment with a temperature of 23±2°C and a relative humidity of 50±10% for 48 hours, and then subjected to performance testing;

[0089] The melt index is tested according to ISO 1133 standard;

[0090] The tensile strength is tested according to ASTM D638 standard;

[0091] The bending strength is tested according to ASTM D790 standard;

[0092] The notched impact strength is tested according to ASTM D256 standard;

[0093] The heat deformation temperature is tested according to ASTM D648 standard;

[0094] Flame retardancy is tested according to the test specified in UL-94 standard;

[0095] The test results are shown in Table 2.

[0096] Table 2

[0097]

[0098] It can be seen from the results in Table 2 that the degradable PPE / PBT / PBS alloy material prepared in the present invention has significantly better impact resistance, flame retardancy, fluidity, wear resistance and temperature resistance.

[0099] Test Example 2

[0100] The degradable PPE / PBT / PBS alloy materials prepared in the above examples and comparative examples were subjected to a natural composting degradation simulation test, and the method is as follows:

[0101] Organic matter from kitchen waste and other food scraps, broken into irregular biodegradable alloy parts, are mixed and piled in the holes dug in advance, covered with soil, and controlled with light, water source, composting temperature and other conditions;

[0102] The soil landfill test method is in accordance with the standard requirements of "GB / T 19275-2003 Evaluation of the potential biodegradability and disintegration of materials under the action of specific microorganisms", according to 4.1.3 Method C: Soil landfill test method, and the composting degradation results are shown in Table 3 below.

[0103] Table 3

[0104] Example No. Degradation rate after 12 weeks / % Example 1 88.7 Example 2 89.8 Example 3 89.1 Example 4 91.3 Example 5 92.9 Comparative Example 1 80.3 Comparative Example 2 68.5

[0105] It can be seen from the results in Table 3 that the degradable PPE / PBT / PBS alloy material prepared in the present invention has a significantly better degradation rate in composting.

[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A degradable PPE / PBT / PBS alloy material, characterized in that: The composition is calculated by weight: PPE 5-30 parts, PBT 20-65 parts, PBS 20-60 parts, compatibilizer masterbatch 5-20 parts, photo-oxidation degradation masterbatch 5-30 parts, PVA 2-10 parts, SiC 0.1-3 parts, nano titanium dioxide 1-10 parts, BPO 0.5-8 parts, polyglycolic acid 5-18 parts, anti-hydrolysis agent 0.5-8 parts, CaCO3 0.5-10 parts, super absorbent resin SAP 1-10 parts.

2. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The intrinsic viscosity of the PPE is 0.3-0.6 dl / g.

3. The degradable PPE / PBT / PBS alloy material according to claim 1 or 2, characterized in that: The compatibilizer masterbatch comprises the following components by weight: 40 parts of GMA-St-AN, 10 parts of PPE, 35 parts of PBT, 25 parts of PBS, 2 parts of maleic anhydride, 3 parts of BPO initiator, and 0.5 parts of benzoin; The GMA-St-AN is a terpolymer of styrene-acrylonitrile-glycidyl methacrylate, and in the GMA-St-AN, the content ratio of styrene, acrylonitrile and glycidyl methacrylate is 8:70:

22.

4. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The preparation method of the compatibilizer masterbatch is as follows: The raw materials are weighed according to the weight ratio and put into a high-speed mixer, stirred at a speed of 300 rpm for 2 to 5 minutes, and after being evenly mixed, they are blended and extruded through a twin-screw extruder, cooled, pelletized, and dried; wherein the temperature of the twin-screw extruder is 200 to 250° C., and the screw speed is 35 to 55 Hz.

5. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The photo-oxidative degradation masterbatch comprises the following components by weight: 70-85 parts of powder, 1-5 parts of PLA, 10-20 parts of PBAT, and 0.1-1 parts of additives; And / or, the relative density of the PVA is 1.26-1.31 g / cm 3 , viscosity is 68.0~78.

0.

6. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The nano titanium dioxide has an average particle size of 5 nm, a TiO2 content of 99.8%, and a specific surface area of ​​350 m 2 / g, bulk density is 0.2g / cm 3 .

7. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The melting point of the anti-hydrolysis agent is 50-53°C.

8. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The average particle size of the CaCO3 is 2000 mesh.

9. The degradable PPE / PBT / PBS alloy material according to claim 1, characterized in that: The average particle size of the super absorbent resin SAP is 60-200 meshes.

10. A method for preparing a degradable PPE / PBT / PBS alloy material as claimed in any one of claims 1 to 9, characterized in that: The raw materials are weighed according to the weight ratio, put into a high-speed mixer for mixing, and then blended and extruded through a twin-screw extruder, cooled, pelletized, and dried; The mixing treatment conditions at least meet the following requirements: the stirring speed is 300 rpm and the time is 2 to 5 min; The parameter settings of the twin-screw extruder at least meet the following requirements: temperature is 190-250° C., and main engine speed is 35-45 Hz.

Citation Information

Patent Citations

  • Flame retardant polybutylene terephthalate / polyphenylene oxide blend alloy and preparation method thereof

    CN103788590A

  • Degradable plastic with good stability and preparation method thereof

    CN112063149A

  • Degradable plastic with good heat resistance and preparation method thereof

    CN112063152A

  • PPE alloy material with arc resistance, tracking resistance and high flame retardance

    CN114231015A

  • High-toughness PPE / PPS alloy material and preparation method thereof

    CN118685019A